Innovation capabilities and human development competitiveness in education sector: Evidence from UAE - Al Dulaimi, Ashraf M. Zedan; Al Marzooqi, Sultan Mohamed; Lubis, Asmuliadi; Siren, Norrodzoh Binti Hj; Kassim, Sayyid Buhar (Frontiers in Psychology, 2022)
Grounded in Human Capital Theory, this study aims to investigate the role of innovation capabilities in human development competitiveness in the education sector of UAE. Based on the qualitative research approach data were collected through interviews with 70 experts and leaders working in this field of HDI and Innovation development in the UAE in order to more comprehensively recognize the main dilemmas involved in the phenomenon under investigation. Furthermore, it applied the conceptual statistics of key performance indicators (KPIs) collected to analyze the UAE’s HDI, innovation capabilities, and human development competitiveness from 2014 to 2020. Results revealed insightful lessons for policy makers and scholars working in innovation management and Sustainable development goals area. Especially, this research will bring key policy directions and future research avenues for better innovative capabilities development in the education sector in developing and low-income economies.